Peyronie's disease and the first user experience of Peyroflex® - G. V. Shirin; N. A. Fedorova (Вестник урологии, 2021)
The article deals with the current issues of the etiology, pathogenesis and clinical course of Peyronie's disease. The diagnostic possibilities of using ultrasound sonography are demonstrated. The international data on known treatment options for Peyronie's disease are reviewed. The author describes his own user experience of the Peyroflex® at an early stage of the disease and gives a preliminary assessment of its effectiveness.